Interpretation of Coagulation Test Results Using a Web-Based Reporting System. - Quesada, Andres E.; Jabcuga, Christine E.; Nguyen, Alex; Wahed, Amer; Nedelcu, Elena; Nguyen, Andy N. D. (Laboratory Medicine)
Background: Web-based synoptic reporting has been successfully integrated into diverse fields of pathology, improving efficiency and reducing typographic errors. Coagulation is a challenging field for practicing pathologists and pathologists-in-training alike. Objective: To develop a Web-based program that can expedite the generation of a individualized interpretive report for a variety of coagulation tests. Methods: We developed a Web-based synoptic reporting system composed of 119 coagulation report templates and 38 thromboelastography (TEG) report templates covering a wide range of findings. Results: Our institution implemented this reporting system in July 2011; it is currently used by pathology residents and attending pathologists. Feedback from the users of these reports have been overwhelmingly positive. Surveys note the time saved and reduced errors. Conclusion: Our easily accessible, user-friendly, Web-based synoptic reporting system for coagulation is a valuable asset to our laboratory services.